Functional Expression of the Human Glucose Transporters GLUT2 and GLUT3 in Yeast Offers Novel Screening Systems for GLUT-Targeting Drugs - Schmidl, Sina; Tamayo Rojas, Sebastian A.; Iancu, Cristina V.; Choe, Jun-Yong; Oreb, Mislav (Frontiers in Molecular Biosciences, 2021)
Human GLUT2 and GLUT3, members of the GLUT / SLC2 gene family, facilitate glucose transport in specific tissues. Their malfunction or misregulation is associated with serious diseases, including diabetes, metabolic syndrome, and cancer. Despite being promising drug targets, GLUTs have only a few specific inhibitors. To identify and characterize potential GLUT2 and GLUT3 ligands, we developed a whole-cell system based on a yeast strain deficient in hexose uptake, whose growth defect on glucose can be rescued by the functional expression of human transporters. The simplicity of handling yeast cells makes this platform convenient for screening potential GLUT2 and GLUT3 inhibitors in a growth-based manner, amenable to high-throughput approaches. Moreover, our expression system is less laborious for detailed kinetic characterization of inhibitors than alternative methods such as the preparation of proteoliposomes or uptake assays in Xenopus oocytes. We show that functional expression of GLUT2 in yeast requires the deletion of the extended extracellular loop connecting transmembrane domains TM1 and TM2, which appears to negatively affect the trafficking of the transporter in the heterologous expression system. Furthermore, single amino acid substitutions at specific positions of the transporter sequence appear to positively affect the functionality of both GLUT2 and GLUT3 in yeast. We show that these variants are sensitive to known inhibitors phloretin and quercetin, demonstrating the potential of our expression systems to significantly accelerate the discovery of compounds that modulate the hexose transport activity of GLUT2 and GLUT3.